On the Limits of Chronological Age - Rainer Kotschy; David E. Bloom; Andrew J. Scott (CESifo GmbH, 2024)
Analysis of population aging is typically framed in terms of chronological age. However, chronological age itself is not necessarily deeply informative about the aging process. This paper reviews literature and conducts empirical analyses aimed at investigating whether chronological age is a reliable proxy for physiological functioning when used in models of economic behaviour and outcomes. We show that chronological age is an unreliable proxy for physiological functioning due to appreciable differences in how aging unfolds across people, health domains, and over time. We further demonstrate that chronological age either fails to predict economic variables when used in lieu of physiological functioning, or that it predicts additional effects on economic behavior and outcomes that are largely unrelated to physiological aging. Continued reliance on chronological age as a proxy for physiological functioning might impede the ability of societies to fully harness the benefits of increasing longevity.
Keywords: I10; I30; J10; 330; population aging; chronological aging; physiological aging; physiological functioning; longevity